Normal Coordinate Analysis of 5-Methyl-2-Thiouracil - Krishnakumar, V.; Balachandran, V. (Asian Journal of Chemistry, 2010)
The normal coordinate analysis of 5-methyl-2-thiouracil has been carried out by assuming Cs point group symmetry. The vibrational spectrum is interpreted on the basis of force field calculations and potential energy distributions.